Digital Platforms and Algorithmic Subjectivities - Armano, Emiliana; BRIZIARELLI, Marco; RISI, Elisabetta (University of Westminster Press, 2022)
Algorithms are a form of productive power - so how may we conceptualise the newly merged terrains of social life, economy and self in a world of digital platforms? How do multiple self-quantifying practices interact with questions of class, race and gender? This edited collection considers algorithms at work - for what purposes encoded data about behaviour, attitudes, dispositions, relationships and preferences are deployed - and black box control, platform society theory and the formation of subjectivities. It details technological structures and lived experience of algorithms and the operation of platforms in areas such as crypto-finance, production, surveillance, welfare, activism in pandemic times. Finally, it asks if platform cooperativism, collaborative design and neomutualism offer new visions. Even as problems with labour and in society mount, subjectivities and counter subjectivities here produced appear as conscious participants of change and not so much the servants of algorithmic control and dominant platforms.